2018
DOI: 10.26499/mab.v11i1.48
|View full text |Cite
|
Sign up to set email alerts
|

Politeness, Speech Act, and Discoure in Sasak Community

Abstract: Politeness, speech act and discourse have become an interest area of language use in context. Attention has been drawn to the universality of politeness strategies across the culture. This study examines the nature of pattern of communication in terms of politeness, speech acts and discourse in Sasak speech community. The subject of the study is 1 Tuan Guru giving religious speech in Sikur village. Participant observation is used as the method of data collection in this study. A video recording was used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In this research, Javanese speech politeness are found in greeting expressive speech acts. In line with Junaidi [10] that asserts that the nature of expression, particularly greeting as one subcategory of acknowledgment, is utilized by speakers to show joy in meeting the audience and Then, the most dominant expressive speech act found in this research is thanking expressive speech act. However, Seviyani & Pujiati [25] found that the function of speech expressed a lot is the function of apologizing (to express guilt).…”
Section: Resultssupporting
confidence: 65%
“…In this research, Javanese speech politeness are found in greeting expressive speech acts. In line with Junaidi [10] that asserts that the nature of expression, particularly greeting as one subcategory of acknowledgment, is utilized by speakers to show joy in meeting the audience and Then, the most dominant expressive speech act found in this research is thanking expressive speech act. However, Seviyani & Pujiati [25] found that the function of speech expressed a lot is the function of apologizing (to express guilt).…”
Section: Resultssupporting
confidence: 65%